Eclecticism in Architecture of Masjid Bandaraya Kuching, Malaysia - Bambang, Karsono; Dona Rose, Koesmeri; Julaihi, Wahid; Saleh, Basim M (IOP Publishing Ltd, 2021)
The eclecticism approach is unconsciously applied in the design process by selecting elements considered as the best elements from different architectural styles or eras to produce a new distinctive building model commonly applied by architects in design. Nowadays, the combination of various architectural elements from different styles into one building is often created, especially in Malaysia. In this research, the author focuses on the design of mosques in Kuching. Throughout history, the Masjid Bandaraya Kuching (known as Masjid Bahagian Kuching by the locals) has undergone four (4) stages of transformation process since it was first built in 1840 A.D until the latest changes that took place in 1968 A.D. This study aims to reveal the eclecticism approach applied in every stage. Qualitative method is applied in this research by examining the photographs from the archives and analysing the longitudinal timeline and cases through the history of Kuching, literature and observations concerning the Masjid Bandaraya Kuching to understand the initial forms and changes that have occurred from the past to the present. The analysis takes into account both comparative and contextual analytical techniques to represent a close interpretation. Findings indicate that the building of Masjid Bandaraya Kuching has been transformed through the traditional eclecticism as well as radical eclecticism approach.